Pemanfaatan Media Daring Google Form untuk Evaluasi Pembelajaran Mufradat di Masa Pandemi Covid-19 - Aris Widada; Lustia Bekti Rohayati; Rina Sarifah (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Pandemi Covid-19 mendorong pemerintah untuk terus berupaya menemukan strategi pembelajaran daring yang tepat melalui pemanfaatan teknologi informasi komunikasi (TIK). Salah satunya adalah penggunaan aplikasi Google Form. Penelitian ini bertujuan menyelidiki pembuatan dan penggunaan evaluasi pembelajaran melalui Google Form. Penelitian ini menggunakan metode evaluatif dan pendekatan kualitatif untuk menghasilkan data terkait penggunaan Google Form dalam pembuatan evaluasi pembelajaran mufradat bahasa Arab. Hasil penelitian membuktikan bahwa Google Form layak digunakan sebagai media evaluasi pada proses pembelajaran mufradat bahasa Arab, di mana skor validasi ahli media adalah 81,5% pada kategori sangat valid dan skor validasi ahli materi adalah 85,3% pada kategori sangat valid. The government continues to aggressively implement several strategies and learning models along with the outbreak of the Covid-19 virus. So that currently there are models and strategies in education which must carry out online/online learning processes by utilizing technology media (ICT). At this time technology continues to develop rapidly and up-to-date, this requires educators to be able to take advantage of it. Through these developments, besides being able to be used for the learning process, it can also be used in learning evaluations, and an easy-to-use application in this case is Google Form. The purpose of this research is to find out how to use and make learning evaluation media with the help of Google Form. By using evaluative methods and qualitative approaches, it is expected to be able to produce data in the form of how to use or utilize Google Forms in evaluating Arabic learning and how to make it. The results of this study in dicate that Google Form is appropriate to be used as an evaluation medium in the Arabic mufradat learning process. This is reinforced from the results of the responses sourced from the validation of media experts, which obtained a score of 81.5% which was included in thecategory very valid, after that from the material expert validation with a score of 85.3% which was included in thecategory very valid.